PENERAPAN SISTEM INFORMASI PERJALANAN DINAS PADA KANTOR KOMUNIKASI DAN INFORMATIKA KABUPATEN BANGGAI BERBASIS WEB - Yeti Kule; Yanto Naim (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah IX Sulawesi, 2021)
The public's need for information has developed very rapidly, thus encouraging the creation of innovations to support very sophisticated and rapidly growing technology in society. The research method used by the author in this study is using the Field Method (Observation) by observing by observing and studying the existing problems. The interview method (Interview) is to do questions and answer with the employees and the head of the service, and the library method is to collect data related to official travel information. It is hoped that the presence of this information system can help employees at the Banggai Regency Communication and Information Office in processing official travel data so that the resulting information can be processed more quickly, accurately, and accurately